Rational Solver
0 votes
55.0k views
If $I=\lim _{x \rightarrow 0} \sin \left(\frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}\right)$, then limit

(A) does not exist

(B) exists and equals 1

(C) exists and equals 0

(D) exists and equals $\frac{1}{2}$
in WBJEE 2021 by Expert (2.4k points) | 55.0k views

1 Answer

0 votes
Best answer

$$I=\lim _{x \rightarrow 0} \sin \left(\frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}\right)$$

Note that $\sin$ is a continuous function. Thus we have 

$$I=\lim _{x \rightarrow 0} \sin \left(\frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}\right)=\sin \left(\lim _{x \rightarrow 0} \frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}\right)$$

Now we calculate the limit by using L'Hopital Rule

$$\begin{aligned}\lim _{x \rightarrow 0} \frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}& = \lim _{x \rightarrow 0} \frac{\mathrm{e}^{x}-1-x}{2x} && \left[ \text{Again $\frac{0}{0}$ form}\right] \\  & = \lim _{x \rightarrow 0} \frac{\mathrm{e}^{x}-1}{2}  \\ &=0\end{aligned}$$

Therfore, we get $$I=\sin \left(\lim _{x \rightarrow 0} \frac{\mathrm{e}^{x}-x-1-\frac{x^{2}}{2}}{x^{2}}\right)=\sin\left(0\right)=0.$$

Hence the correct option is (C).

by Expert (2.4k points)
selected by
Welcome to Rational Solver, where you can ask questions and receive answers from other members of the community.
51 questions
10 answers
1 comment
1,801 users